PENGARUH PERUBAHAN KOMPONEN LAPORAN ARUS KAS, PERUBAHAN LABA KOTOR, DAN PERUBAHAN SIZE PERUSAHAAN TERHADAP EXPECTED RETURN SAHAM - Serly C; Astuti Yuli Setyani (Jurnal Riset Akuntansi dan Keuangan, 2011)
The purpose of this study was to examine the effect of changes in thecomponents of cash flows (operating cash flow changes, investment cashflow changes , cash flow funding changes), changes in gross profit,and change the size of the company toward expected return stock ofmanufacturing companies which go public in Indonesia Stock Exchange. The number of companies studied as many as 84 companies listed in Indonesia Stock Exchange with the observation period from 2004 to 2008. The technique used in the data analysis is the technique of multiple linear regression. Results of the study showed that only cash flow operations changes ,investment cash flow changes and gross margin changes that showed significantly influence against expected return stockKata kunci: expected return, size, arus kas operasi, arus kas investasi, laba kotor